2015
DOI: 10.1111/ecoj.12327
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Surveillance Cameras on Crime: Evidence from the Stockholm Subway

Abstract: I study the effects of surveillance cameras on crime in the Stockholm subway system. Beginning in 2006, surveillance cameras were installed in subway stations at different points in time. Difference‐in‐difference analysis reveals that introduction of the cameras reduced crime by approximately 25% at stations in the city centre. The types of crimes deterred by cameras are planned crime, that is, pickpocketing and robbery. It is also shown that some of the crimes were displaced to surrounding areas. The cost of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 14 publications
(23 reference statements)
0
42
1
3
Order By: Relevance
“…The paper also contributes additional evidence of the effectiveness of monitoring to an emerging literature on the role of CCTV cameras in combating crime (Priks 2014(Priks , 2015King, Mulligan, and Raphael 2008;Farringdon 2009, 2003).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The paper also contributes additional evidence of the effectiveness of monitoring to an emerging literature on the role of CCTV cameras in combating crime (Priks 2014(Priks , 2015King, Mulligan, and Raphael 2008;Farringdon 2009, 2003).…”
mentioning
confidence: 87%
“…5 The effectiveness of CCTV cameras in reducing crime is a current topic, with million dollars being spent in this public safety infrastructure. Priks (2014Priks ( , 2015 document the causal effects of CCTV cameras on unruly behavior and some types of crime, using temporal variation in CCTV installation in Swedish stadiums and underground. King, Mulligan, and Raphael (2008) showed that property crime was reduced as a result of CCTV monitoring on the streets of San Francisco.…”
mentioning
confidence: 99%
“…For example, an analysis by the National Highway Traffic Safety Administration (NHTSA 1998) reports that the marking of car parts and the consequent drop in the theft of marked cars corresponded to a rise in theft rates for unmarked cars. Similarly, Priks (2009) establishes that the installation of surveillance cameras in the Stockholm subway displaced crime to the surrounding area. However, there also is empirical evidence to the contrary.…”
Section: Motivation and Main Resultsmentioning
confidence: 99%
“…Most of the research on cameras in crime prevention is conducted in the UK and the US (Welsh & Farrington, 2009), but a small number of Swedish and Norwegian research does exist: Mikael Priks conducted Swedish studies on the effects of public surveillance on criminal behavior in the subways of Stockholm (Priks, 2015) and on unruly behavior in football stadiums throughout the country (Priks, 2014). Both his analyses show a reduction in antisocial behavior that can be attributed to the cameras.…”
Section: Place-based Police Strategies and Interventionsmentioning
confidence: 99%